(untitled) (Journal of the College of Basic Education, 2022)
A coin has two sides. Steganography although conceals the existence of a message but is not completely secure. It is not meant to supersede cryptography but to supplement it. The main goal of this method is to minimize the number of LSBs that are changed when substituting them with the bits of characters in the secret message. This will lead to decrease the distortion (noise) that is occurred in the pixels of the stego-image and as a result increase the immunity of the stego-image against the visual attack. The experiment shows that the proposed method gives good enhancement to the steganoraphy technique and there is no difference between the cover-image and the stego-image that can be seen by the human vision system (HVS), so this method can be considered a success and can be adopted in the field of steganography